Exposure of Stored Packed Erythrocytes to Nitric Oxide Prevents Transfusion-associated Pulmonary Hypertension. (November 2016) - Muenster, Stefan; Beloiartsev, Arkadi; Yu, Binglan; Du, E; Abidi, Sabia; Dao, Ming; Fabry, Gregor; Graw, Jan A.; Wepler, Martin; Malhotra, Rajeev; Fernandez, Bernadette O.; Feelisch, Martin; et al.
Abstract : Background: Transfusion of packed erythrocytes stored for a long duration is associated with increased pulmonary arterial pressure and vascular resistance. Prolonged storage decreases erythrocyte deformability, and older erythrocytes are rapidly removed from the circulation after transfusion. The authors studied whether treating stored packed ovine erythrocytes with NO before transfusion could prevent pulmonary vasoconstriction, enhance erythrocyte deformability, and prolong erythrocyte survival after transfusion. Methods: Ovine leukoreduced packed erythrocytes were treated before transfusion with either NO gas or a short-lived NO donor. Sheep were transfused with autologous packed erythrocytes, which were stored at 4°C for either 2 ("fresh blood") or 40 days ("stored blood"). Pulmonary and systemic hemodynamic parameters were monitored before, during, and after transfusion. Transfused erythrocytes were labeled with biotin to measure their circulating lifespan. Erythrocyte deformability was assessed before and after NO treatment using a microfluidic device. Results: NO treatment improved the deformability of stored erythrocytes and increased the number of stored erythrocytes circulating at 1 and 24 h after transfusion. NO treatment prevented transfusion-associated pulmonary hypertension (mean pulmonary arterial pressure at 30 min of 21 ± 1 vs . 15 ± 1 mmHg in control and NO–treated packed erythrocytes, P < 0.0001). Washing stored packed erythrocytes before transfusion did not prevent pulmonary hypertension. Conclusions: NO treatment of stored packed erythrocytes before transfusion oxidizes cell-free oxyhemoglobin to methemoglobin, prevents subsequent NO scavenging in the pulmonary vasculature, and limits pulmonary hypertension. NO treatment increases erythrocyte deformability and erythrocyte survival after transfusion. NO treatment might provide a promising therapeutic approach to prevent pulmonary hypertension and extend erythrocyte survival. Abstract : In an ovine model, pretreatment of stored packed erythrocytes with nitric oxide before transfusion increases their survival after transfusion, prevents increases in pulmonary vascular resistance, and may provide a potential approach to mitigate adverse effects of stored erythrocyte transfusions.Supplemental Digital Content is available in the text.